Employee Performance in Public Sector: A Bibliometric Analysis of Global Trends and Thematic Development - Elagaili, Tareq Alambrouk; Azam, S. M. Ferdous; Tham, Jacquline; Khatibi, Ali (International Review of Management and Marketing, 2025)
The study intends to thoroughly analyse employee performance in the institutions of public sector. It also investigates the factors that affected employee performance during the period from 1974 to 2025. This study analyzed 175 out of 294 documents sourced from the two largest databases, Web of Science and Scopus, to get the desired outcome. The research examined the scientific output of publications, prolific authors, influential papers, institutions and nations, keyword co-occurrence, thematic mapping, co-citations, and collaborations among authors and countries. The research used “VOS viewer” software to analysis and thematic clustering. The results indicated that 2024 and 2021 were the most prolific years, with 40 and 23 publications, respectively. Ghent University in Ghent, Belgium, is the most organisation institution, while the United States is the most influential country. The research determined that Public Personnel Management is the preeminent journal based on total citations and publications. Five theme clusters of employee performance in the public sector were identified. The study provides guidance and information to academics regarding the current status of employee performance in the public sector and delineates future research directions in this field of study. The impotence of the study arises from its status as the first study to offer a performance analysis and scientific mapping of employee performance in the public sector utilizing a multilabel database.